A Functional Clock Within the Main Morning and Evening Neurons of D. melanogaster Is Not Sufficient for Wild-Type Locomotor Activity Under Changing Day Length - Menegazzi, Pamela; Beer, Katharina; Grebler, Verena; Schlichting, Matthias; Schubert, Frank K.; Helfrich-Förster, Charlotte (Frontiers in Physiology, 2020)
A major challenge for all organisms that live in temperate and subpolar regions is to adapt physiology and activity to different photoperiods. A long-standing model assumes that there are morning (M) and evening (E) oscillators with different photoreceptive properties that couple to dawn and dusk, respectively, and by this way adjust activity to the different photoperiods. In the fruit fly - Drosophila melanogaster, M and E oscillators have been localized to specific circadian clock neurons in the brain. Here, we investigate under different photoperiods the activity pattern of flies expressing the clock protein PERIOD (PER) only in subsets of M and E oscillators. We found that all fly lines that expressed PER only in subsets of the clock neurons had difficulties to track the morning and evening in a wild-type manner. The lack of the E oscillators advanced M activity under short days, whereas the lack of the M oscillators delayed E activity under the same conditions. In addition, we found that flies expressing PER only in subsets of clock neurons showed higher activity levels at certain times of day or night, suggesting that M and E clock neurons might inhibit activity at specific moments throughout the 24 hours. Altogether, we show that the proper interaction between all clock cells is important for adapting the flies’ activity to different photoperiods and discuss our findings in the light of the current literature.